2014
DOI: 10.1103/physreve.90.063016
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous scaling of passive scalar fields advected by the Navier-Stokes velocity ensemble: Effects of strong compressibility and large-scale anisotropy

Abstract: The field theoretic renormalization group and the operator product expansion are applied to two models of passive scalar quantities (the density and the tracer fields) advected by a random turbulent velocity field. The latter is governed by the Navier-Stokes equation for compressible fluid, subject to external random force with the covariance ∝δ(t-t')k(4-d-y), where d is the dimension of space and y is an arbitrary exponent. The original stochastic problems are reformulated as multiplicatively renormalizable f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(95 citation statements)
references
References 99 publications
11
77
0
7
Order By: Relevance
“…Fortunately, despite the difference between the formalism for density and tracer fields in the case of a compressible fluid, the critical dimensions for these two fields have the same form; for detailed analysis see [21]. Thus, expressions (9) and (10) remain true for tracer field as well.…”
Section: Tracer Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, despite the difference between the formalism for density and tracer fields in the case of a compressible fluid, the critical dimensions for these two fields have the same form; for detailed analysis see [21]. Thus, expressions (9) and (10) remain true for tracer field as well.…”
Section: Tracer Fieldmentioning
confidence: 99%
“…Usually d plays a passive role -see [20] for Navie-Stokes equation itself and [21,22] for advection of scalar fields -but if d = 4, the situation is similar to the analysis of the incompressible Navier-Stokes equation near space dimension d = 2. In this case an additional divergence appears in the 1-irreducible Green's function �v ′ v ′ � 1-ir , see [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been shown in [1] and discussed in [14], the model (5) - (6) is invariant with respect to the Galilean symmetry, which results to the UV finitness of the two Green's functions:…”
Section: Feynman Diagrammatic Techniquementioning
confidence: 98%
“…They can be absorbed by a suitable local counterterm v i ∇ 2 v i , and a regular expansion in both y and ε = d − 2 was constructed. Up to now the present model (5) has been investigated at the fixed space dimension d = 3, for which the action (5) contains all terms that can be generated during the renormalization procedure [1,[13][14][15]. However, using the dimensional analysis it can be shown that at d = 4 there appears an additional divergence, also in the Green's function v v .…”
Section: Quarks-2016mentioning
confidence: 99%